Nauczanie zdalne w dobie pandemii koronawirusa SARSCoV- 19 a doznania stresowe w grupie nauczycieli - Pudełko, Karolina; Płonka, Joanna (Studia Edukacyjne, 2021)
Remote education in the era of the coronavirus pandemic was a challenge many teachers were not prepared for. The challenge and a number of changes that the transition to remote education has triggered may have resulted in additional stressful experiences for the teaching profession. This article is a theoretical and research paper and its purpose is to draw a picture of these experiences, to identify the stressors in the remote teaching situation and to examine the general level of stress currently experienced by teachers. The study involved 66 teachers working at different levels of education. A diagnostic survey (online questionnaire) and Plopa and Makarowski’s PSQ (Perceived Stress Questionnaire) examining emotional tension, external stress, intrapsychic stress and general level of perceived stress were used as the research method. The study outcomes show that some teachers may experience emotional tension, an increased feeling of fatigue, irritability or an accompanying lack of energy. However, it seems that the situation of transitioning to remote teaching did not outweigh the ability, resources or capacity of the teachers surveyed to meet the demands placed on them under the circumstances.